Factors of Policy for “Teman Bus” Program with “Buy The Service” Scheme in Bandung City - Risma Pitriani Nuryana; Nandang Alamsah Deliarnoor; Neneng Yani Yuningsih (Universitas Sultan Ageng Tirtayasa, 2024)
Bandung is the 3rd metropolitan city and one of the main tourist destinations in Indonesia, which provides various benefits, such as opening up employment opportunities because there are various business fields that are developing. It also increases cultural preservation because increasing tourism interest can provide incentives to preserve the heritage, culture, and history of an area. However, despite these various benefits, the high number of tourists often makes traffic jams worse. Therefore, at the end of 2021, the government launched “Teman Bus” programme with the Buy the Service (BTS) scheme as a new breakthrough that is expected to not only be able to overcome traffic jams but also reduce pollution, supports reform in the transportation sector and can be a means of changing people's behaviour from one that tends to be conventional to one that is more digitally literate. However, the fact is that up to the time the research was conducted, there were still many Bandung residents who had not chosen to switch from private transportation to mass transportation services, so the researchers tried to take an approach using the six implementation variables proposed by Van Meter and Van Horn to find out what factors influenced the course of this policy.